Security of energy supply in the European Union measured by REES and CERE indices - Dudek, Pavel; Klosová, Anna, 1942-; Taušer, Josef; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2014)
This thesis tries to summarize current situation in the European Union from the perspective of security of energy supply. In the first part I summarize development of security of energy supply legislation in the European Union, in the second part I compare different methods used to measure security of energy supply and in the third part I use two indices CERE and REES (Contribution to EU risk exposure, Risky External Energy Supply) and measure risk exposure and its development for particular countries between years 2006 and 2012.
Vedoucí práce: Anna Klosová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: diplomové práce; master's theses; economics of globalisation and european integration [obor dipl. práce]